Gemcitabine Alone versus combination of Gemcitabine and Cisplatin for the Treatment of Patients with Locally Advanced and/or Metastatic Pancreatic Carcinoma: A Retrospective Analysis of multicenter study - Inal, A.; Kos, F. T.; Algin, E.; Yildiz, R.; Dikiltas, M.; Unek, I. T.; Isikdogan, A. (Aepress Sro, 2012)
The majority of patients with pancreatic cancer is of advanced disease. Several randomized Phase II and III trials suggest that the combination of gemcitabine and cisplatin (GemCis) response rates were higher than Gemcitabine (Gem) alone, however the trials were not enough powered to indicate a statistically significant prolongation of survival in patients with advanced pancreatic adenocarcinoma. The aim of this retrospective multicenter study is to evaluated the efficiency of Gem alone versus GemCis in patients with locally advanced and/or metastatic pancreatic adenocarcinoma. A total of 406 patients, from fourteen centers were evaluated retrospectively. All patients received Gem or GemCis as first-line treatment between September 2005 to March 2011. Primary end of this study were to evaluate the toxicity, clinical response rate, progression-free survival (PFS) and overall survival (OS) between the arms. There were 156 patients (M: 98, F: 58) in Gem arm and 250 patients (M: 175, F: 75) in the combination arm. Gemcitabin arm patients older than the combination arm ( median 63 vs 57.5, p=0.001). In patients with the combination arm had a higher dose reduction (25.2% vs 11.3%, p=0.001) and dose delay (34% vs 16.8%, p=0.001). Among patients with the combination and Gemcitabin arm gender, diabetes mellitus, performance status, cholestasis, grade, stage did not have a statistically difference (p>0.05). Clinical response rate to the combination arm was higher than the Gem arm (69.0% vs 49.7%, p=0.001). PFS was more favorable in the GemCis arm than Gem alone, but the difference did not attain statistical significance (8.9 vs 6.0, p=0.08). OS was not significantly superior in the GemCis arm (12.0 vs 10.2, p>0.05). Grade III-IV hematologic and nonhematologic toxicity were higher in the combination arm. PFS was more favorable in the GemCis arm than Gem alone, but the difference did not attain statistical significance. OS was not significantly superior in the GemCis arm.
Keywords: advanced pancreatic cancer; first-line chemotherapy; gemcitabine; cisplatin